Trade and Innovation Project: A Synthesis Paper - Onodera, Osamu (OECD Publishing, 2008)
This paper, together with five case studies, is a part of a larger project looking at the various effects that trade and investment can have on innovation. The study looks at the role of trade and investment in technology transfer, the competition effects of trade and investment on innovation as well as economies of scale. The study also looks at Global Value Chains as an organisational innovation in its own right, which is supported by a freer trade and investment environment. The study also forms a contribution to the OECD Innovation Strategy launched at the OECD Ministerial Council Meeting in 2007
Keywords: Trade